Time-sharing measurements of ionospheric electron temperature and electron density with the electric field using double probes: An experiment on the Antarctic sounding rocket S-310JA-7 - Ogawa, Toshio; Makino, Masahiko; Yamagishi, Hisao; Fukunishi, Hiroshi; Hirasawa, Takeo; Kodera, Kunihiko (1982)
P(論文) An experiment was carried out of a time-sharing measurement of auroral ionospheric electric field, electron temperature and electron density with double probes on board the Antarctic sounding roket S-310JA-7 on March 27,1978 at Syowa Station. The measurements of each element are compared with each other, and the electron temperature and density are compared with the other independent measurements which were made simultaneously on board the same rocket. The principle of the measurement of electron temperature and density with double probes is described in detail in the Appendix. departmental bulletin paper